Pemecahan Masalah Matematika Dengan Inovasi Berbasis IT Di SDK Marsudirini Tambolaka - Setiawi, Agustina Purnami; Kurra, Titus (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2023)
Mathematics is often considered difficult by many people in everyday life, especially indicated by the level of student learning achievement that tends to be lower than other subjects, especially in Southwest Sumba Regency. The high level of complexity and demands for analysis make most students avoid math. Mathematical problem solving is an important skill that every student must have, because it is always related to problems that demand solutions. This article proposes an innovative approach using Information Technology (IT) to facilitate understanding of mathematical concepts, visualization of problems, as well as providing interactive exercises and instant feedback. The training method at SDK Marsudirini Tambolaka involves lectures, group discussions and practical exercises. Through this collaborative learning, students are expected to overcome obstacles in understanding and solving math problems. The results of the training showed positive responses from the Principal, teachers, staff and students, indicating the success of the implementation. By continuing to develop this initiative, it is hoped that STIMIKOM Stella Maris Sumba can continue to provide quality mathematics education and in accordance with technological developments. The school hopes that there will be further training activities related to Mathematical Problem Solving with IT-based Innovation at SDK Marsudirini Tambolaka to continue to improve students' math skills..